A Systematic Review of the Adoption of eHealth Cloud-based Technology Applications during COVID-19 - Malatji, William Ratjeana; VanEck, Rene; Zuva, Tranos (International Journal of Advanced Science Computing and Engineering, 2021)
Electronic health technology applications are important tools that are utilized to provide health care services. These applications allow healthcare professionals and patients to share, manage and have control over their health information electronically whilst maintaining social distancing. Under hard conditions brought by the coronavirus 2019 disease (COVID-19), eHealth tools can be used to assist with the provision of healthcare services. However, the adoption of these technology applications by users is still questionable. This study presents a systematic literature review of 31 articles that were published on the adoption of eHealth cloud-based technology applications during COVID-19. A systematic literature review was conducted using PRISMA protocol by searching the Scopus databases. The search was conducted for the year 2020 to 2021 since COVID-19 is still new in the research field. From 31 articles that were selected, it was found that most countries are still left behind on this topic. It was only a few researchers in each country who tried to contribute or put effort into the topic. Furthermore, it was indicated that Italy contributed the highest with 5 authors to this topic. Thus, more research still needs to be conducted on this topic. One of the limitations of this study was that, the data was gathered from the Scopus database only. Researchers suggest that for future research, other additional sources need to be searched to find out more about the adoption of eHealth cloud-based technology applications during COVID-19.